OPTIMIZING BLOOD COLLECTION SYSTEMS: ISSUES AND SOLUTIONS FOR LABORATORIES AND MANUFACTURERS - NAWAF ASMAIR ALMUTAIRI, MOHANAD ABDULRAOUF SERAJ, JEHAN HAMAD BEN HYZAAM, DIMA AHMED ALI ALHARBI, ABDULAZIZ MOHAMMED ABDULAZIZ ALANGARI, BASHRA MANA JERWAN ALSHAMMARI, ASRAR IBRAHIM ALSHOMRANI; WEJDAN TALAL SAJINI, WEJDAN MAHMOUD ALSINDI, ABDULRAHMAN ZAID ALNOAIMI, ISRAA ATIAH ALQURAYQIRI, MOHAMMED ABDULLAH SHUJAA, FAYHA THAIEB ALMUTAIRI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: The pre-analytical phase is the most vulnerable to errors in laboratory testing, with blood collection tube (BCT) components—including tube materials, additives, separators, and closures—serving as a significant source of interference that can compromise test accuracy. This review examines the impact of these components on clinical assays and proposes collaborative solutions for laboratories and manufacturers. Methods: A comprehensive analysis of current literature was conducted to identify documented interferences caused by BCT components across various clinical applications, including therapeutic drug monitoring (TDM), coagulation testing, hormone immunoassays, and specialized testing for biomarkers and trace elements. Results: Key issues identified include the adsorption of lipophilic analytes onto plastic surfaces and gel separators, leading to falsely decreased concentrations in TDM; leaching of stopper components (e.g., plasticizers, magnesium) causing interference in immunoassays and coagulation tests; and variable performance of clot activators affecting electrolyte and hormone measurements. Innovations such as chemically modified plastics, mechanical separators, and hybrid tubes offer promising solutions by reducing analyte adsorption and improving sample integrity. The lack of global standardization and the commodity-driven market pose significant challenges to the adoption of improved technologies. Conclusions: Optimizing blood collection systems is critical for diagnostic accuracy. Clinical laboratories must implement rigorous tube validation and standardized procedures, while manufacturers should enhance material disclosure and pursue collaborative innovation. A concerted effort from all stakeholders is essential to mitigate pre-analytical errors, improve the reliability of laboratory results, and enhance patient care.